Non-traumatic chest pain in young adults: a medical audit. Issue 3 (September 1990) - Luke, L C; Cusack, S; Smith, H; Robertson, C E; Little, K
Abstract : Four hundred consecutive young patients who attended an accident and emergency department with non-traumatic chest pain as their primary complaint were reviewed. They represented 0.7% of total new attendances. Most were self-referrals, but ambulance transport was requested for over 25%. The majority of investigations (mainly chest radiography and electrocardiography) performed in this group of patients were normal; however, almost one in six investigations was judged to be abnormal. Although this group of patients is at low risk for serious cardiorespiratory disease, a small but significant number of underlying (mainly non-cardiac) disorders was found and 22.5% (90) required in-patient admission. In contrast, almost one-fifth of patients received no specific diagnosis, while almost 40% were deemed to require no follow-up.